Deutschland, Russland, Komintern. I. Überblicke, Analysen, Diskussionen. Neue Perspektiven auf die Geschichte der KPD und die deutsch-russischen Beziehungen (1918-1943) - Drabkin, Jakov (Archive des Kommunismus - Pfade des XX. Jahrhunderts, 2013)
Thanks to the archival revolution, relations between the Comintern, the Soviet government and the KPD (German Communist Party) now appear in a new light. Careful analyses contextualize this history against the backdrop of the simultaneously published volume of sources. This project undertaken by the German-Russian Historical Commission contributes significantly to a transnational understanding of German communism and German-Soviet relations.